2013
DOI: 10.14310/horm.2002.1448
|View full text |Cite
|
Sign up to set email alerts
|

Sequential treatment with teriparatide and strontium ranelate in a postmenopausal woman with atypical femoral fractures after long-term bisphosphonate administration

Abstract: ObJEctIVE: Despite the existence of numerous case series, no evidenced-based medical management for atypical fractures associated with bisphosphonate (bP) treatment has been established. DEsIGN: We report the outcome of teriparatide (trP) administration followed by strontium ranelate (sr) in a woman with a complete and an incomplete contralateral atypical fracture of the femoral diaphysis (AFF) associated with bP treatment. the spontaneous complete AFF was managed with intramedullary nailing, discontinuation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…(75,76) In the past few years, numerous case reports and small prospective studies have reported healing of AFF or ONJ, typically occurring within a few months of starting teriparatide therapy. (97)(98)(99)(100) In addition, a few reports have demonstrated a beneficial effect of strontium ranelate in AFF. (97)(98)(99) Based on available reports, a limited course of teriparatide may be considered to accelerate healing of BP-related AFFs or ONJ, consistent with the recommendations of the ASBMR Task Force on Atypical Femoral Fractures and the International Consensus report on ONJ.…”
Section: Management Of Adverse Events Related To Bisphosphonatesmentioning
confidence: 99%
“…(75,76) In the past few years, numerous case reports and small prospective studies have reported healing of AFF or ONJ, typically occurring within a few months of starting teriparatide therapy. (97)(98)(99)(100) In addition, a few reports have demonstrated a beneficial effect of strontium ranelate in AFF. (97)(98)(99) Based on available reports, a limited course of teriparatide may be considered to accelerate healing of BP-related AFFs or ONJ, consistent with the recommendations of the ASBMR Task Force on Atypical Femoral Fractures and the International Consensus report on ONJ.…”
Section: Management Of Adverse Events Related To Bisphosphonatesmentioning
confidence: 99%
“…In one case report of sequential therapy with TPTD and SR in a patient with alendronate associated-AFF, the authors concluded that sequential treatment was successful and may be a rational treatment option in managing incomplete AFF (Lampropoulou-Adamidou et al, 2013). In this case, TPTD therapy was delayed for 11 months following fixation of a complete AFF, however, the patient sustained an incomplete contralateral AFF during treatment with TPTD and 22 months following the first AFF.…”
Section: Discussionmentioning
confidence: 99%
“…PTH has been proposed as an intervention for recalcitrant AFFs and has already been used off-label clinically in several case reports and case series. (10,(15)(16)(17) PTH has also been used in the context of AFF in an individual with osteogenesis imperfecta, another condition associated with long-term bisphosphonate usage. (18) However, the capacity of PTH to remobilize BP in a fracture and the mechanism underlying improved healing remain unclear.…”
Section: Discussionmentioning
confidence: 99%